2021
DOI: 10.1016/j.redox.2021.102041
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV2 infection impairs the metabolism and redox function of cellular glutathione

Abstract: Viral infections sustain their replication cycle promoting a pro-oxidant environment in the host cell. In this context, specific alterations of the levels and homeostatic function of the tripeptide glutathione have been reported to play a causal role in the pro-oxidant and cytopathic effects (CPE) of the virus. In this study, these aspects were investigated for the first time in SARS-CoV2-infected Vero E6 cells, a reliable and well-characterized in vitro model of this infection. SARS-CoV2 markedly decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 52 publications
3
93
0
1
Order By: Relevance
“…Several reviews mentioned the possibility of ROS elimination for treatment of COVID-19. Although in one case, the application of N-acetylcysteine (NAC), a ferroptosis inhibitor that promotes glutathione supplementation, restored glutathione levels in the SARS-CoV-2-infected cells, and markedly reduced C-reactive protein (CRP) levels in a severe COVID-19 patient, and another randomized clinical trial indicated that a high dose of NAC brought little benefit to hindering the evolution of severe COVID-19 [65][66][67]. However, our results here showed that the ferroptosis inhibitor suppressed inflammatory cytokines release and MHV-A59 propagation in murine macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews mentioned the possibility of ROS elimination for treatment of COVID-19. Although in one case, the application of N-acetylcysteine (NAC), a ferroptosis inhibitor that promotes glutathione supplementation, restored glutathione levels in the SARS-CoV-2-infected cells, and markedly reduced C-reactive protein (CRP) levels in a severe COVID-19 patient, and another randomized clinical trial indicated that a high dose of NAC brought little benefit to hindering the evolution of severe COVID-19 [65][66][67]. However, our results here showed that the ferroptosis inhibitor suppressed inflammatory cytokines release and MHV-A59 propagation in murine macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In these conditions, the non-oxidative phase of PPP is increased, in which glycolysis intermediates are converted into the ribose-5-phosphate required for the synthesis of the nucleic acids, which is necessary for the virus replication [25,26]. In addition, high levels of oxidized glutathione and a significant decrease in enzymes forming part of the cellular defense line against oxidative stress were found, including superoxide dismutase 1 (SOD1), glucose-6-phosphate dehydrogenase, and peroxiredoxin [27][28][29]. RBCs from COVID-19 could, therefore, be more exposed to the attack of reactive oxygen species (ROS), resulting in induced cellular lysis and inability to carry oxygen.…”
Section: Covid-19 and Rbcs Metabolismmentioning
confidence: 99%
“…However, blocking glutathione synthesis did not change the progress of SARS-CoV-2 infection, suggesting increased GSH may be an epiphenomenon or can only function in a microenvironment in vivo [ 42 ]. In contrast, the detection of SARS-CoV-2 infected cells 24 h after infection indicated impaired biosynthesis of GSH [ 45 ]. A possible explanation is that increased methylation demands caused by SARS-CoV-2 infection give priority to utilize substrates for glutathione synthesis to generate methyl-groups [ 46 ].…”
Section: Metabolism Reprogramming In Covid-19 Infectionmentioning
confidence: 99%